The role of co-products in biorefinery sustainability: energy allocation versus substitution method in rapeseed and carinata biodiesel chains. (1st May 2015) - D'Avino, Lorenzo; Dainelli, Riccardo; Lazzeri, Luca; Spugnoli, Paolo
Abstract: The paper analyzes biodiesel chains of rapeseed ( Brassica napus ) and carinata ( Brassica carinata ) cultivated in Central and Southern Italy, assessing the impact on Global Warming Potential by means of the Life Cycle Assessment methodology. The production chains differed in use of the oilcake, as animal feed for rapeseed and as biofumigant for B. carinata . The allocation of emissions across co-products was first calculated on the basis of their energy content according to the criterion proposed by European Commission for biofuel production. The resulting impacts were then compared to those obtained through the substitution approach (system expansion method), which considers emissions that are saved by replacing the equivalent conventional product with co-product bio-based materials i.e. soybean meals, nematicidal fumigants, fertilizers and glycerol. The results showed that this method is sensitive to pointing out the importance of the valorization of co-products to the sustainability of bioenergy supply chain. Among the different options taken into consideration, in the case of the B. carinata biodiesel chain, the substitution of conventional fumigants and fertilizers with biofumigants and amendments is able to determine a global net saving of 134 g CO2 eq per MJ of biodiesel, reversing the sustainability assessment obtained through the energy allocation method. Overall, the results suggest that, when planning future biorefineries, environmental assessment should take the substitution approach into account in order for valorization of co-products and diversification of processes to be rewarded. Highlights: The co-products valorization should improve the biorefinery sustainability assessment. This occurs in carbon footprint of biodiesel from rapeseed and carinata. Carinata oilcake could be valorized in formulation of biobased amendments. Including biofumigants, the saving vs diesel by energy allocation in Mediterranean Area is 50%. Notably, biodiesel becomes even carbon-negative applying the system expansion method.